Reconstituting Social License to Operate: TGI's Response to the Grissik–Duri Gas Pipeline Incident - Sahat Parlindungan Simarmata (Politeknik Siber Cerdika Internasional, 2026)
Background: The gas pipeline leak incident on the Grissik–Duri (GD) KP222 line in Selensen, Kemuning District, Indragiri Hilir Regency, Riau, on January 2, 2026, caused a technical, social, and operational crisis that had the potential to affect PT Transportasi Gas Indonesia's (TGI) Social License to Operate (SLO). Objective: This study analyzed how TGI's SLO was reconstituted after the incident by comparing the effectiveness of technical mitigation and social resolution and examining their implications for the company's social legitimacy. Methods: Using a qualitative case study design, the analysis drew on twelve publicly available documents published between January and April 2026, comprising national media reports, sectoral energy news coverage, and government releases selected based on their direct relevance to the incident chronology, response, and recovery. Data were analyzed thematically through data reduction, narrative display, and conclusion drawing, with credibility strengthened through source triangulation. Results: TGI managed the technical crisis by closing the safety valves, extinguishing the fire within approximately 13 hours, restoring operations within six days, and completing pipeline integrity testing before restarting operations. Socially, the company and relevant stakeholders conducted victim assistance, community consultations, and compensation processes. However, technical success and procedural settlements have not guaranteed sustainable public trust recovery. Conclusion: TGI's post-incident SLO position remains closer to vulnerable acceptance than approval. This study extends the application of SLO theory to post-incident energy infrastructure management and emphasizes the need to integrate measurable social indicators into oil and gas crisis-management systems to sustain legitimacy and operational continuity.